Touched by Venus: The Concept and Treatment of Syphilis in the First Half of the 20th Century Lithuania - Skujytė-Razmienė, Asta (Tautosakos darbai, 2025)
In this article, using studies by the Lithuanian and foreign medical historians, data from archaeological research conducted in Lithuania, and the interwar press, I delve into the history of a new disease appearing in Europe at the end of the 15th century – syphilis – in order to answer the question, why this disease, in spite of the number of patients, which grew extremely rapidly in Lithuania in the first half of the 20th century and caused great concern among doctors and general public, practically left no traces in the Lithuanian folklore. I assume that the lack of material about syphilis in our folklore could have been determined by the complexity of diagnosing this disease, including its sexual nature as an uncomfortable and shameful topic. The conducted research enables me to confirm this hypothesis, because, as testified by the collected material, in the first half of the 20th century, especially in the provinces, syphilis was likely not to be distinguished from other diseases (e. g. skin diseases), so this sexually transmitted infection could be treated in the same way as other diseases. In addition, among the people, catching the “French” disease was considered a great shame, which could result in exclusion of the sufferer from the community.
Keywords: syphilis; venereal diseases; history of medicine; folk medicine